2014
DOI: 10.1016/j.actpsy.2014.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Sequential aiming with one and two limbs: Effects of target size

Abstract: It is well reported that movement times to the first target in a two-target sequence are slower than when a single target response is required. This one-target advantage has been shown to emerge when the two-target sequence is performed with the same limb and when the first and second segments within the sequence are performed with different limbs (i.e., when there is a switch between limbs at the first target). The present study examined the functional dependency between response segments in both single and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(48 reference statements)
1
3
0
Order By: Relevance
“…Consistent with previous research on upper limb sequential aiming movements in the TD population (Adam et al, 2000;Adam, Helsen, Elliott, & Buekers, 2001;Adam, Paas, Eyssem, Slingerland, Bekkering, & Drost, 1995;Helsen, Adam, Elliott, & Buekers , 2001;Khan, Mottram, Adam, & Buckolz, 2010;Mottram, Khan, Lawrence, Adam, & Buckloz, 2014), Lawrence et al (2013) have revealed that individuals with DS treat movements within a sequence as functionally dependent actions. The research revealed a one target movement time advantage for both the TD population and individuals with DS.…”
supporting
confidence: 88%
“…Consistent with previous research on upper limb sequential aiming movements in the TD population (Adam et al, 2000;Adam, Helsen, Elliott, & Buekers, 2001;Adam, Paas, Eyssem, Slingerland, Bekkering, & Drost, 1995;Helsen, Adam, Elliott, & Buekers , 2001;Khan, Mottram, Adam, & Buckolz, 2010;Mottram, Khan, Lawrence, Adam, & Buckloz, 2014), Lawrence et al (2013) have revealed that individuals with DS treat movements within a sequence as functionally dependent actions. The research revealed a one target movement time advantage for both the TD population and individuals with DS.…”
supporting
confidence: 88%
“…To investigate this further, future research should explicitly measure both the variability of movement endpoints together with the variability of movement kinematics throughout the trajectory of movement (for a review see Khan et al, 2006). Whilst speculative, one might reasonably predict that in two target single hand extension movements, the endpoint variability of movement one would be significantly less than those of single target movements (see Mottram et al, 2014). In addition, processes within both the movement constraint and the movement integration hypothesis would predict that participants would likely spend significantly more time after peak velocity and that trajectory kinematics would show greater use of online adjustments in the two target single hand extension movements compared to single target movements.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the factors that influence the nature of the interdependency between segments has been of considerable interest to researchers (Adam et al, 2000;Cullen et al, 2001;Khan, Mottram, Adam, & Buckolz, 2010;Khan, Sarteep, Mottram, Lawrence, & Adam, 2011;Lavrysen, Helsen, Elliott, & Adam, 2002;Lavrysen et al, 2003;Lawrence, Reilly, Khan, Mottram, & Elliott, 2013;Mottram, Khan, Lawrence, Adam, & Buckolz, 2014). The aim of the present study was to differentiate between the processes underlying the integration between movement segments at central cognitive and peripheral neuromuscular levels by examining the interactive effects of switching hands and movement direction at the first target.…”
mentioning
confidence: 99%
“…Whereas several researchers have focused their efforts on the relationship between RT and the number of response segments (e.g., Fischman, 1984;Henry & Rogers, 1960;Klapp et al, 1974;Sternberg et al, 1978), Adam and colleagues have extensively studied the time it takes to execute sequential aiming movements (Adam et al, 1993(Adam et al, , 1995(Adam et al, , 2000(Adam et al, , 2001Adam & Paas, 1996). The OTA:MT has been shown to emerge across levels of practice (Lavrysen et al, 2003), regardless of participants' handedness or hand used (Helsen et al, 2001;Lavrysen et al, 2003), when vision is available or occluded (Lavrysen et al, 2002), and when there is a switch in limbs at the first target (Khan et al, 2010;Mottram et al, 2014).…”
Section: Introductionmentioning
confidence: 99%